Mobile health (mHealth) based medication adherence measurement – a pilot trial using electronic blisters in diabetes patients. (6th September 2013) - Brath, Helmut; Morak, Jürgen; Kästenbauer, Thomas; Modre‐Osprian, Robert; Strohner‐Kästenbauer, Hermine; Schwarz, Mark; Kort, Willem; Schreier, Günter
Abstract : Aims: The aim of the present study was to evaluate a mobile health (mHealth) based remote medication adherence measurement system (mAMS) in elderly patients with increased cardiovascular risk treated for diabetes, high cholesterol and hypertension. Cardiovascular risk was defined as the presence of at least two out of the three risk factors: type 2 diabetes, hypercholesterolaemia and hypertension. Methods: For treatment of diabetes, hypercholesterolaemia and hypertension, four predefined routinely used drugs were selected. Drug adherence was investigated in a controlled randomized doctor blinded study with crossover design. The mAMS was used to measure and improve objectively the adherence by means of closed‐loop interactions. Results: The mean age of the 53 patients (30 female) was 69.4 ± 4.8 years. A total of 1654 electronic blisters were handed out. A statistically significant difference ( P = 0.04) between the monitoring and the control phase was observed for the diabetes medication only. In a post‐study questionnaire twenty‐nine patients appreciated that their physician knew if and when they had taken their medications and 13 asked for more or automated communication with their physicians. Only one subject withdrew from the study because of technical complexity. Conclusions: The results indicate that mHealth based adherence management is feasible and well accepted by patients with increased cardiovascular risk. It may help to increase adherence, even in patients with high baseline adherence and, subsequently, lead to improved control of indicators including blood pressure and cholesterol concentrations. Electronic blisters can be used in a multi‐medication regimen but need to be carefully designed for day‐to‐day application.